Evaluasi Aspek Fisik dan Kenyamanan Pedestrian di Jalan Diponegoro Salatiga melalui Persepsi Masyarakat - Henny Mustika Wati; Nugraheni Widyawati (Jurnal Lanskap Indonesia, 2019)
Pedestrian track on Jalan Diponegoro Salatiga when 2017th has suffered by some damage and has not been functioned properly. Pedestrian track is used for trading activities and for parking area. Therefore is needed to inspect with research analysis. The research was carried on February till March 2017 on Jalan Diponegoro Salatiga. The research is evaluation of physical and comfort aspect of pedestrian of Jalan Diponegoro Salatiga based on the public perception. The purpose are knowing public perception about the physical and amenitu aspect, knowing maintener priority and knowing the appropriate pedestrian track based on the result of perception and priority handling with redesain. The type of research is descriptive qualitative. Stages from research are observation, questionnaires with 100 respondents, analysis and redesign. Analysis of questionnaire using performance and importance analysis. Making redesign using sketchup software based on the results of perception and the regulations. The results of the public perception is physical of pedestrian track on Jalan Diponegoro Salatiga was low and amenity the pedestrian was good enough. The results performance and importance analysis is vegetation nursing, lamp function of pedestrian track, condition of paving, and cleaness of pedestrian track are being main priority for repair and the maintainer give more attention. Keywords: amenity, evaluation, pedestrian, physical aspects, public perception